P374 Prediction of an adverse cardiovascular response to physical exercise from resting echocardiography imaging in young adults with suboptimal blood pressure. (17th January 2020) - Alsharqi, M; Huckstep, O J; Williamson, W; Mohamed, A; Tan, C; Lapidaire, W; Telles, F; Arnold, L; Monteiro, C; Dawes, H; Foster, C; Lewandowski, A J; et al.
Abstract: Funding Acknowledgements: British Heart Foundation (BHF) grants (PG/13/58/30397) Background: Young adults with mildly elevated blood pressure are less likely to engage with physical activity. This may be because early hypertension alters myocardial response to moderate exercise, leading to greater perceived exertion and lower levels of enjoyment. As atrial and ventricular function are closely coupled we investigated whether subclinical atrial changes at rest may identify this myocardial response. Purpose: To identify whether subclinical changes in left atrial function at rest predict response to exercise by performing left atrial deep-phenotyping in a cohort of young adults with a range of blood pressures. Methods: Seventy-one full-term born young adults (25.25 ± 5.13 years) were enrolled in the Young Adult Cardiovascular Health sTudy (YACHT) to undergo baseline clinical and cardiovascular phenotyping including detailed blood pressure measurement. Cardiopulmonary exercise testing combined with echocardiography imaging was performed to assess the myocardial response to physical exercise at 40%, 60% and 80% of peak exercise load for all participants. Left ventricular ejection fraction and global longitudinal strain were measured from an apical four chamber view at each exercise load, and resting left atrial phasic function was assessed by conventional and speckle tracking echocardiography from apical four and two chamber views (figure 1). Results: In this young cohort with a range of blood pressure (120.9 ± 12.96/70.85 ± 9.78 mmHg), resting left atrial reservoir and conduit function, but not left atrial structural measures, showed good correlation with left ventricular ejection fraction and global longitudinal strain during 40%, 60% and 80% of peak exercise. The association between resting left atrial conduit with left ventricular deformation at 60% of peak exercise intensity remained significant when adjusted for age, sex and mean arterial pressure (P = 0.007). Conclusion: Left atrial phasic function at rest predicts left ventricular responses to physical exercise in this cohort of young adults, which may relate to early subclinical left atrial remodelling in early hypertension. These findings require validation in other cohorts and investigation of whether this exercise limitation can be overcome in young hypertensives.